HUKUM ISLAM PERSPEKTIF FILSAFAT ILMU - Kurtucy, M. Husen; Zaynuri, Muhammad; Rahmatullah, Muhammad Asep; Mas’ud, Muhammad; Nuraeni, Neni (DESANTA (Indonesian of Interdisciplinary Journal), 2025)
This study explores Islamic law from the perspective of the philosophy of science, positioning it not merely as a normative legal system but as a comprehensive and philosophical body of knowledge. Islamic law is analyzed through the three main aspects of the philosophy of science—ontology, epistemology, and axiology—to reveal its foundational structure and philosophical uniqueness in comparison to other legal systems. Ontologically, Islamic law originates from divine will as manifested in the Qur’an and Sunnah. Epistemologically, it is constructed through a synthesis of revelation and reason, employing methods such as ijtihad, qiyas, and ijma’ in its legal formulation. Axiologically, Islamic law aims to realize justice, public welfare, and life balance based on the concept of maqashid al-shari’ah. This research adopts a qualitative approach using a literature study method and content analysis techniques on both classical and contemporary sources. The findings indicate that Islamic law, when understood within the framework of the philosophy of science, represents a dynamic, adaptive, and continuously relevant system of knowledge that remains faithful to its core principles. This study contributes to the development of a more reflective, scientific, and contextual discourse on Islamic law.